F-18-FDG PET in presurgical oro-maxillofacial carcinomas - Aigner, Reingard M. (Radiology and oncology (Ljubljana), 2002)
Background. We performed an analysis of the diagnostic impact of F-18-FDG-PET in presurgical oro-maxillofacial malignancies. Patients and methods. The diagnosis of the malignant primary was made clinically and was histological- ly verified before FDGPET and the cervical CT examinations were performed in 25 patients of this study. For the FDG-PET investigation a full ring PET scanner was used (ECAT EXACT HR+, Siemens). Thoracic CT was performed only if pathological findings on FDG-PET scans required it. Results. The primary was clearly identified with FDG-PET in all patients. Active cervical lymph node sites were seen in 9/25 patients (ipsilateral: 8/25; ipsi- and contralateral: 1/25). Lung-metastases were found in 2/25 patients. Cervical CT: The primary was recognised in all patients. Artefacts caused by dental implants did not allow visualising the extension of the tumour in 9/25 patients. Ipsilateral lymph node sites were seen in 7/25 patients (size: 0.9-1.6 cm), and ipsiand contralateral lymph node sites in 7/25 patients (size: 0.8-1.8 cm). The lung metastases primarily recognised with FDG were visualised with CT in both patients, too. Conclusion. FDG-PET is a sensitive diagnostic modality for the preoperative visualisation of active, i.e. suspicious malignant lymph nodes. Distant metastases were demonstrated in 8% of the patients on whole body PET. The usefulness of FDG-PET and CT for establishing the diagnosis of the primaryis limited. The preoperative importance of CT lies primarily in the accessibility of the algorithms for the intraoperative recon- struction of thefacial structures.
Keywords: Diagnosis; diagnostika; Fluorine Radioisotopes; Fluorovi radioizotopi; Maksilarne novotvorbe; Maxillary Neoplasms; Mouth Neoplasms; onkologija; Pathology; Radiography; radiološka diagnostika; rak (medicina); Tomografija emisijska-računalniška; Tomografija radiografska, računalniška; Tomography, Emission-Computed; Tomography, X-Ray Computed; Usta, novotvorbe